1998
DOI: 10.1136/gut.42.6.823
|View full text |Cite
|
Sign up to set email alerts
|

Responses to gastric distension in functional dyspepsia

Abstract: Background-Studies have shown that an altered visceral perception threshold plays a role in the pathogenesis of upper gastrointestinal tract symptoms in dyspeptic patients. However, it is not clear whether the compliance and adaptive relaxation of the proximal stomach contribute to the symptoms. Aims-To investigate whether abnormal relaxation or adaptation of the proximal stomach during the interdigestive state and the postprandial phase could explain the symptoms of functional dyspepsia. Subjects-Twelve volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(122 citation statements)
references
References 21 publications
3
118
0
1
Order By: Relevance
“…Scintigraphic and ultrasonographic studies have demonstrated an abnormal intragastric distribution of food in patients with functional dyspepsia, with preferential accumulation in the distal stomach, [29][30][31] and gastric barostat studies have confirmed reduced proximal gastric relaxation in response to a meal in patients with functional dyspepsia. 11,32 A relationship between impaired gastric accommodation and early satiety and weight loss has been reported by some 11,33,34 but has not been confirmed in other studies. 35 The prevalence of impaired accommodation is particularly high in patients with acute-onset dyspepsia, and this has been attributed to a defect at the level of gastric intrinsic nitrergic neurons.…”
Section: Impaired Gastric Accommodationmentioning
confidence: 87%
“…Scintigraphic and ultrasonographic studies have demonstrated an abnormal intragastric distribution of food in patients with functional dyspepsia, with preferential accumulation in the distal stomach, [29][30][31] and gastric barostat studies have confirmed reduced proximal gastric relaxation in response to a meal in patients with functional dyspepsia. 11,32 A relationship between impaired gastric accommodation and early satiety and weight loss has been reported by some 11,33,34 but has not been confirmed in other studies. 35 The prevalence of impaired accommodation is particularly high in patients with acute-onset dyspepsia, and this has been attributed to a defect at the level of gastric intrinsic nitrergic neurons.…”
Section: Impaired Gastric Accommodationmentioning
confidence: 87%
“…Several pathophysiological causes of FD have been identified, such as delayed gastric emptying (Gilja et al, 1996;Quartero et al, 1998;Kusunoki et al, 2010;Karamanolis et al, 2006), abnormal antroduodenal motility (Stanghellini et al, 1992;Kusunoki et al, 2000), altered sensitivity to duodenal acid or lipid exposure (Burbera et al, 1995;Samson et al, 1999), visceral hypersensitivity (Mertz et al, 1998;Undeland et al, 1998), and impaired accommodation reflex (Salet et al, 1998;Tack et al, 1998). Among these, an impaired accommodation reflex is the most frequently observed pathophysiological condition in patients with FD.…”
Section: Figmentioning
confidence: 99%
“…The gastric compliance in W/W v animals was greater than the increase in compliance when muscarinic receptors were blocked in wildtype animals, suggesting that factors other than cholinergic tone contribute to gastric tone (i.e., other excitatory peptide neurotransmitters or the stretch sensitivity of IC-IM). Abnormal compliance is observed in some human gastric disorders (Salet et al, 1998), and it is would be interesting to determine whether these patients have defects in the numbers or function of IC-IM.…”
mentioning
confidence: 99%